2016
DOI: 10.1249/mss.0000000000000923
|View full text |Cite
|
Sign up to set email alerts
|

Neural Contributions to Muscle Fatigue

Abstract: During exercise, there is a progressive reduction in the ability to produce muscle forces. Processes within the nervous system, as well as within the muscles contribute to this fatigue. In addition to impaired function of the motor system, sensations associated with fatigue, and impairment of homeostasis can contribute to impairment of performance during exercise. This review discusses some of the neural changes that accompany exercise and the development of fatigue. The role of brain monoaminergic neurotransm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
212
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 390 publications
(220 citation statements)
references
References 97 publications
7
212
0
1
Order By: Relevance
“…Muscle fatigue is characterized by an increase of active motor units (De Luca, 1997), which is usually reflected by an increase in EMG amplitude signals in submaximal muscle contractions. A recent review has shown that muscle fatigue induced by a submaximal isometric contraction is associated with variable responses in motor units firing rates according to the intensity of the fatiguing task (Taylor et al, 2016). For example, motor unit behavior during submaximal isometric contraction at moderate intensity (50% MVC), which correspond to the Sorensen test (Demoulin et al, 2006), is first associated with a decrease in firing rate followed by an increased motor units recruitment (Heckman and Enoka, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle fatigue is characterized by an increase of active motor units (De Luca, 1997), which is usually reflected by an increase in EMG amplitude signals in submaximal muscle contractions. A recent review has shown that muscle fatigue induced by a submaximal isometric contraction is associated with variable responses in motor units firing rates according to the intensity of the fatiguing task (Taylor et al, 2016). For example, motor unit behavior during submaximal isometric contraction at moderate intensity (50% MVC), which correspond to the Sorensen test (Demoulin et al, 2006), is first associated with a decrease in firing rate followed by an increased motor units recruitment (Heckman and Enoka, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This centrally-mediated increase in central motor drive would also increase perceived effort (Finn et al, 2018; McNeil et al, 2011). If an increase in neural drive into the cortex or motoneuron is not possible (e.g., during a maximal voluntary contraction, MVC) or insufficient to compensate for the diminished corticospinal excitability, the ability of the central nervous system to recruit motor units would be reduced and result in a lower muscle activation which is generally referred to as central fatigue (Klass et al, 2008; Martin et al, 2006; Petersen et al, 2003; Taylor et al, 2016). As central fatigue limits single-joint and whole body exercise performance (Hureau et al, 2018b; Taylor et al, 2006), it is important to understand how physical activity and associated fatigue influences the integrity of the corticospinal pathway.…”
Section: Significance Of the Corticospinal Pathwaymentioning
confidence: 99%
“…Although the use of an intermittent MVC task was necessary to estimate the variation of VA throughout the task and between treatments, the large amount of peripheral fatigue generated, as estimated by the decrease of Ptw (see Figures 2 and 3), may have partially masked tDCS effects. Indeed, in such a condition, the limiting factor of performance may be more peripheral than central (Taylor et al, 2016), which could have limited the centrally mediated action of tDCS on performance.…”
Section: Limitationsmentioning
confidence: 99%
“…Central fatigue can be defined as "a progressive reduction in voluntary activation of muscle during exercise" (Gandevia, 2001). A part of the central fatigue can be explained by a progressive reduction of the brain capacity to activate the muscle maximally (Taylor, Amann, Duchateau, Meeusen, & Rice, 2016). Interestingly, studies on tDCS have sometimes reported opposite effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation